Corporate Entrepreneurship Strategy Initiative at Gojek Indonesia - Nadhiva, Meliniarta; Purnomo, Margo; Purbasari, Ratih (Yayasan Mitra Peduli Indonesia, 2024)
Corporate entrepreneurship becomes an innovation and creativity in solving problems and finding opportunities to improve business processes and enhance organizational performance. This study aims to explore successful corporate entrepreneurship initiatives at Gojek Indonesia to enhance competitiveness and provide added value to Gojek users and partners. This study uses a qualitative method with a literature review to identify, evaluate, and interpret all relevant sources. The results show that an innovative organizational culture, visionary leadership, and adequate resource availability support Corporate Entrepreneurship (CE) at Gojek. Gojek Indonesia has successfully implemented various innovative corporate entrepreneurship initiatives, such as developing GoPay and GoFood products, strategic partnerships with Tokopedia, and employee empowerment through training and development programs. The positive impact of corporate entrepreneurship at Gojek is evident in various aspects, including increased innovation and creativity, higher adaptability, operational efficiency, more comprehensive market penetration, increased customer loyalty and satisfaction, and long-term growth and sustainability. Therefore, corporate entrepreneurship is a critical element of modern business strategy that helps companies stay relevant and competitive and provide added value to users, partners, and the broader community